Perceived training gaps of newly licensed veterinarians and impact of participation in a peer-facilitated quality assurance program in Ontario, Canada: interviews with peer advisors - Brunt, Michael W.; Wycherley, Kate; Gohar, Basem (Frontiers in Veterinary Science, 2026)
Newly graduated and newly licensed veterinarians possess the knowledge and skill required to practice medicine but often struggle to translate that knowledge and skill in a clinical setting without additional supports. The objectives of this exploratory pilot study were to explore the preparedness to practice of newly licensed veterinarians by understanding the perceived potential knowledge or skills gaps and to describe the perceived impact of participation in a peer-facilitated quality assurance program from the perspective of the peer advisors. Semi-structured interviews were conducted with peer advisors (n = 10), audio-recorded, transcribed verbatim, and inductively analyzed using Applied Thematic Analysis. Study participants identified perceived gaps in skills and training that may exist for newly licensed veterinarians, including non-clinical professional skills (e.g., communication, self-care) and volume of clinical skills (e.g., species-specific surgery, internal medicine), which may negatively impact their preparedness to practice. Study participants described participation in the peer-facilitated quality assurance program as encouraging self-reflection and continued improvement throughout licensees’ careers rather than traditional in-clinic peer mentorship aimed at improving clinical and non-clinical confidence and proficiency. Study participants described a desire to beneficially influence the profession through helping other veterinarians and their own positive feelings that resulted from their participation in the peer-facilitated quality assurance program. Program participation provided positive experiences for peer advisors and perceived positive experiences for licensees while encouraging learning through self-reflection. There are elements in the Peer Advisory Conversation program that lend itself to being integrated into existing or future peer mentorship programs.